189k views
1 vote
3 + 2x -y =0
-3 -7y = 10x​

1 Answer

5 votes

Answer:

(-1, 1)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination
  • Solving systems of equations by graphing

Explanation:

Step 1: Define systems

3 + 2x - y = 0

-3 - 7y = 10x

Step 2: Rewrite systems

3 + 2x - y = 0

  1. Add y to both sides: 3 + 2x = y

Step 3: Redefine systems

y = 2x + 3

-3 - 7y = 10x

Step 4: Solve for x

Substitution

  1. Substitute in y: -3 - 7(2x + 3) = 10x
  2. Distribute -7: -3 - 14x - 21 = 10x
  3. Combine like terms: -14x - 24 = 10x
  4. Add 14x on both sides: -24 = 24x
  5. Divide 24 on both sides: -1 = x
  6. Rewrite: x = -1

Step 5: Solve for y

  1. Define original equation: -3 - 7y = 10x
  2. Substitute in x: -3 - 7y = 10(-1)
  3. Multiply: -3 - 7y = -10
  4. Add 3 to both sides: -7y = -7
  5. Divide -7 on both sides: y = 1

Step 6: Graph

Check the solution set.

3 + 2x -y =0 -3 -7y = 10x​-example-1
User Iokevins
by
4.5k points